Prevalence and Risk Factors for Latent Tuberculosis Infection among Health Care Workers in China: A Cross-Sectional Study - Zhang, Xia (Public Library of Science, 2013)
BACKGROUND: Health care workers (HCWs) are at risk of latent tuberculosis infection (LTBI). In China, tuberculosis (TB) is a major public health problem, but the prevalence of LTBI in HCWs especially in the hospital for pulmonary diseases has not been assessed enough. The aim of this study was to determine the prevalence and putative risk factors of LTBI among HCWs in a chest hospital and a TB research institute in China. METHODOLOGY/PRINCIPAL FINDINGS: A cross-sectional study was conducted among HCWs in China in 2012. LTBI was assessed by T-SPOT.TB, and information on HCWs was collected using a standardised questionnaire. Risk factors for LTBI were analyzed by univariate and multivariate regression. The overall prevalence of LTBI among HCWs was 33.6%. Analyzed by job category, the highest prevalence was found among laboratory staff (43.4%). In the different workplaces, the proportion of LTBI was significantly higher among the high risk workplaces (37.4%) compared to the low risk workplaces. The duration of employment had a significant impact on the prevalence of LTBI. Positive T-SPOT.TB test results accounted for 17.6%, 16.8%, 23.5%, 41.8% and 41.6% in groups of ≤2, 3–5, 6–10, 11–20, and >20 working years respectively. In multivariate analysis, job categories (Laboratory staff [2.76 (95% CI: 1.36; 5.60)], technician staff [2.02 (95% CI: 1.12; 3.64)]); working duration as a HCW for 11 to 20 years [3.57 (95% CI: 1.46; 8.71)], and 20 years above [3.41 (95% CI: 1.28; 9.11)]; and the history of household TB contact [2.47 (95% CI: 1.15; 5.33)] were associated with increased risk of LTBI. CONCLUSIONS/SIGNIFICANCE: Prevalence of LTBI estimated by T-SPOT.TB is high among Chinese HCWs and working duration, job category and the history of household TB contact were associated with increased risk. These data highlight adequate infection control measures should be undertaken.